2007
DOI: 10.1093/tropej/fmn100
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencincing Discharge against Medical Advice among Paediatric Patients in Abakaliki, Southeastern Nigeria

Abstract: Discharge against medical advice (DAMA) has become a major problem in health care delivery in Nigeria. Children are the victims because most of the times they are not the one taking the decision, and may not understand or contribute to it. This retrospective study was undertaken to identify the factors that influence DAMA among paediatric patients in Ebonyi State University Teaching Hospital, Abakaliki in southeastern Nigeria, with a view at curbing it. There were 97 cases of DAMA out of a total admission of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 4 publications
5
50
3
4
Order By: Relevance
“…8 Financial constraints and Low socio-economic class also featured prominently as reasons for DAMA in other studies inNigeria. [4][5][6][7][8][9] Gloydet al 14 in their study on DAMA in the paediatric ward of a central hospital in Bouake, Cote D'Ivoire noted a 5 fold increase in DAMA rates occurring simultaneously with an increase in hospital fees. Roodpegma et al 13 in Iran gave financial reasons as the fourth reason for DAMA in their study however most of the patients had health insurance unlike the present study where health care is funded by the parents/guardians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Financial constraints and Low socio-economic class also featured prominently as reasons for DAMA in other studies inNigeria. [4][5][6][7][8][9] Gloydet al 14 in their study on DAMA in the paediatric ward of a central hospital in Bouake, Cote D'Ivoire noted a 5 fold increase in DAMA rates occurring simultaneously with an increase in hospital fees. Roodpegma et al 13 in Iran gave financial reasons as the fourth reason for DAMA in their study however most of the patients had health insurance unlike the present study where health care is funded by the parents/guardians.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been noted that subsequent treatment after DAMA may be more difficult and costly 3 . Discharge against medical advice has commonly been reported in many paediatric centres in Nigeria, [4][5][6][7][8][9][10][11][12] other African countries 14,16 and Asia 13,15 with DAMA prevalence rates ranging from 0.96% 10 to 7.4% 4 . Various reasons for DAMA given have included financial constraints, dissatisfaction with medical care and treatment, parent's impression that child's clinical condition had improved, resort to alternative medicine, lack of trust in orthodox medicine, lack of clinical improvement and inconvenience of child's hospitalisation [4][5][6][7][8][9][10][11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have consistently shown that socio-economic status play a significant role in premature discharges involving both adults and children. 6,8,[9][10][11][12] The prevalence from studies in children ranges between 1-2% in most studies in developing countries that reported retrospective analyses of cases of leaving in-patient care AMA alone 13,14,15 , while higher prevalence was obtained in other reports that included a larger proportion of neonates 6,14 . In some other circumstances children could be taken away from hospital by caregivers without notice of medical staff, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…absconding (elopement), which is considered by some as a form of discharge AMA 12,17 . The commonly associated factors observed in developing countries include poverty, perception of illness improvement and conditions such as HIV, tuberculosis and protein energy malnutrition 6,13,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…It increases the risk of readmission and can lead to complicated problems over the time (Alfandre 2009). Such actions should initiate child protection steps like discussing with and involving child protection agency which might result on legal implication (Ibekwe et al 2008). Many physicians are struggling to balance between trying to respect the patient's right to self-determination and on the other hand, to convince the patients and their families about the best choice of treatment (Paul and Remorino 2010).…”
mentioning
confidence: 99%